Darkland, Fairyland, Gypsyland: ‘Gypsy’ Heterotopias and Barthesian Prestidigitation (Critical Romani Studies, 2026)
This article examines myths that have been disseminated through arts and culture about so-called “Gypsies”, confining them to “anti-worlds”. There is always a “glamour that enwraps the Gypsy race” (Sampson 1935a, 10). Romantics and some nineteenth-century writers considered them to be positive symbols of resistance to newly born capitalism and rampant industrialization. This constituted a sort of “légende rose” (Descola 2019, 13), or pink legend, as Philippe Descola put it about Achouars, that is, a very positive gaze upon a people yet labelled “primitive”. However, this article intends to focus on the negative “black legend” (Ibid.), the idea that “Gypsies” form a dark and hostile people belonging to a dark and hostile fantasized territory. Sixteenth- and seventeenth-century playwrights first depicted “Gypsies” as thieves, monsters, or inferior beings displaying dubious morality. They were ascribed mysterious powers, and “Gypsy” women were depicted as witches connected to their natural and dangerous territory, an occult Gypsyland. In all cases, they were shown as somewhat uncivilized (Grellman 1787, 24) and primitive beings, very much attached to their own traditions: a figure of the “Orientals within” (Lee 2000, 132). This Gypsylorism – understood here broadly as an orientalism about “Gypsies” – imposed a vision about them, now deeply rooted in the collective consciousness of the gadjos. “Gypsies” of fiction have been created and re-created until they occupy, in the Western imagination, foreign and/or dark territories yet these are situated inside Europe.Surprisingly, they can be found to this day wandering in books and movies, in other spaces or “espaces autres”, and in fetishized beyonds or heterotopias (Foucault 1966, 31). “Gypsy” characters inhabit the margins of the dominant societies of the countries in which they settled centuries ago, as if constantly bringing along with them, in the fantasies of the gadjos, their own frontiers which would isolate them from the rest of the population; or they live in exotic Gypsylands inside the very West. Their assigned territories are “absolutely different”, they are counter spaces, or “contre-espaces” (Foucault 1966, 24), constituting a huge reserve of imagination, “une grande réserve d’imagination” (Foucault 1967, 36). A “Gypsy” para-history thus has been told and written over and over again, “evacuating” (Barthes 2010, 240) the history of Gypsies, and questioning the role of artists and responsibility of social players. This article will also seek to raise the issue of “double consciousness” (Du Bois 1903, 8) among “Gypsy” Travellers.
Keywords: Mythology; Heterotopias; Gypsylorism; Romani Studies